Synthesis and Characterization of Pyridine-pyrrole-modified Carbon Nanotube Derivatives via Ylides - Çalışır, Ümit (Current Organic Chemistry, 2025)
The high dipolarophile structure of MWCNT compounds enables them to be used as a reactive 2π member in 1,3-dipolar cycloaddition reactions. N-substituted glycine ester compounds and employed 1,3-dipolar cycloaddition reactions involving azomethine-ylides for the synthesis of multiwalled carbon nanotube compounds that underwent covalent modification. Initially, N-substituted glycine esters (3a) and N-substituted glycine compounds were synthesized. N-substituted glycine (4a) and substituted aromatic aldehyde derivatives were reacted with the dipolarophilic MWCNTs, which have regioselectivity only on (6,6)-bonds, via azomethine ylide intermediates over a 1,3-dipolar cycloaddition reaction to obtain the target pyridine-pyrrole-modified carbon nanotube derivatives (6a-g). The compounds' structural characterizations were achieved using FTIR, Raman, NMR, TEM, UV-VIS, and TGA methods. The dispersibility of the compounds was evaluated in various solvents. The activity of each compound's antimicrobial properties against Escherichia coli was assessed. Based on the obtained results, it was concluded that the compounds, by the method employed, adsorbed Escherichia coli bacteria and decreased the bacterial concentration in their film form. According to the results, the compounds can be used in bacterial adsorption-based purification systems (the eradication of water and environmental pollutants) based on the results obtained.
Keywords: 1; 3-dipolar cycloaddition reactions